Photoelectrochemistry of solution processed hematite nanoparticles, nanoparticle-chains and nanorods - Patil, Supriya A.; Shinde, Dipak V.; Kim, Eun-kyung; Lee, Joong Kee; Mane, Rajaram S.; Han, Sung-Hwan (ROYAL SOC CHEMISTRY, 2012)
We report a coordination chemistry approach for shape-controlled synthesis of alpha-Fe2O3 (hematite) nanostructures. Three distinct morphologies viz. nanoparticles, nanoparticle-chains and nanorods were synthesized from inorganic iron precursor sources of nitrate, sulfate and chloride, respectively, in the presence of urea as a pH regulating agent and were characterized by X-ray diffraction, scanning electron microscopy and Raman spectroscopy. The responsible growth mechanism and possible factors controlling the morphologies are explored. Photoelectrochemical cells constructed by utilizing these nanostructures produced stable photocurrents in iodide electrolyte. The nanoparticle-chains morphology of alpha-Fe2O3 revealed the highest photocurrent density of 0.36 mA cm(-2) at 0 V bias conditions under 1 Sun illumination. The reason for the high performance is investigated with the help of impedance spectroscopy analysis, wherein the electrode composed of nanoparticle-chains affords the lowest charge transfer resistance and thereby the highest photoconversion yield, as compared to those of the nanoparticle and nanorod electrodes.